Formation of Consciousness of Fictional Characters: Reading in the novel Al-Masarrat Wal Awja’ (Joys and Pains) - Jabara, Kawthar Muhammed Ali (Arab Journal for Sciences and Research Publishing, 2021)
The events often contained in any narrative work contribute to the formation of the consciousness of the characters in the work, no matter how superficial that consciousness, as well as the consciousness of the writer that transmits it in one or a group of his works, through his characters who contribute to a set of events and interactions between them by revealing their vision for themselves and each other, in addition to their pronouncement of judgments resulting from their consciousness of what happened in their past and what is happening in their surroundings. Consciousness is one of the most prominent features that we can find in a character that has an independent existence, and has its own style of perceiving situations and facts surrounding it, which lives in its world, as well as realizing what is going on in itself in advance. Hence, we deal with this research of the fictional characters in the novel (Al-Masarrat Wal Awja’) by the Iraqi novelist Fuad al-Takarli from this aspect that was said to have been addressed by critical studies, to reveal a mechanism that shapes these characters’ consciousness of themselves and others, their references and their vision of the world that the author conveys to us through his narrator.Our choice of novel (Al-Masarrat Wal Awja’) was due to the writer’s care of his main and secondary characters and the multiplicity of their social and cultural levels, which enriched the fictional work in terms of the references that each character reflects and refers to, especially the main character (Tawfiq), which we see once existential, once agnostic, and at other times without all the references, in addition to being a sophisticated figure at work and presenting his vision of the world through his diaries that were part of the fictional work.The research is divided into three sections, the first is theoretic and is concerned with the consciousness of the term and the concept, and the second dealt with patterns of consciousness in terms of the concept of each type and how it appeared in the novel under consideration and in which character was it reflected from its characters. As for the last topic, we dealt with the vision of the world presented by the novelist about the path of his main character (Tawfiq), so that the research finally reaches a set of results, the most important of which is that the characters in the novel in question were neither superficial nor an intellectual construction, and this is what led to the formation of the consciousness of each in a different way from the other.
Keywords: Consciousness; A Vision of the World; Fouad Al-Takarly; Fictional Characters; Joys and Sorrows; The Iraqi Novel